Relation of serum and follicular level of BMP15 with Oocyte quality, embryo grading and pregnancy rate - Hashim, Zainab Hassan; Amer, Lubna; Al-Wasiti, Estabraq A. (Journal of Contemporary Medical Sciences, 2022)
Objectives: Use of serum and follicular fluid concentration of oocyte secreted factors BMP15 as biomarkers of oocyte quality, embryo quality and it's relation to pregnancy rate. Methods: Eighty eight women were included in this study; they were selected from those undergoing intra-cytoplasmic sperm injection. Results: Positive pregnancy was achieved by 14 women accounting for 19.0 % (total number of women that reach embryo transfer was 72). No significant difference in mean serum BMP15 between pregnant and non- pregnant women, but the level of follicular fluid BMP15 was significantly higher in pregnant women. MI oocyte count was not significantly correlated to serum or follicular fluid BMP15 (p > 0.05). MII oocyte count showed highly significant positive correlation to serum and follicular fluid BMP15 (p < 0.01). Grade1 embryo count showed highly significant positive correlation to serum and follicular fluid BMP15 (p < 0.01), Grade 2 embryo count showed significant positive correlation to serum BMP15 (p = 0.032), but the grade 2 embryo count showed non- significant correlation to follicular BMP15 (p > 0.05). Also grade 3 embryo count showed non- significant correlation to serum and follicular BMP15 (p > 0.05). Conclusions: The current study revealed that serum and follicular BMP15 could be used as indicator for oocyte maturity, and serum BMP15 could be used as indicator of good quality embryos.